Kemahiran Komunikasi Dalam Kalangan Mahasiswa Akademi Pengajian Islam, Universiti Malaya (APIUM): Isu dan Solusi: Communication Skills Among Students of Academy of Islamic Studies, Universiti Malaya (AISUM): Issues and Solutions - Awaludin, Ain Nabiha; Ali @ Mat Zin, Aizan (Journal Al-Muqaddimah, 2024)
The communication weaknesses of local graduates are often at the end of the pen of employers who interviewed prospective employees for their institutions. The feedback given by the employers has been brought to the attention of the Ministry of Higher Education. Therefore, the Ministry of Higher Education (KPT) introduced the Soft Skills Development Module as an initiative to apply human skills to students, especially communication skills. In connection with this, the university management has taken various steps and interventions to improve generic skills and one of them is communication skills. In addition, this study is conducted to identify issues of communication skills and its solutions to enhance these skills among AISUM students. Data is collected through documentation methods and questionnaires. Stratified random sampling is used to facilitate the distribution of survey forms to respondents consisting of 115 undergraduate students from various academic disciplines at AISUM. Statistical data analysis method benefitted the Statistical Package of Social Science (SPSS) software version 27.0. The findings show that the communication skills of AISUM students are at a moderate level based on student confidence and market capabilities. Communication skills monitoring workshops, active participation in various programmes such as public speaking, debates and others are significant solutions in improving communication skills. In conclusion, AISUM has encouraged the involvement of students in various programmes within and outside the campus as an effort to enhance their communication skills for their future endeavours.